The limits of neoliberalism authority, sovereignty and the logic of competition - Davies, William 1976-; Chakrabortty, Aditya (Los Angeles London SAGE, 2017)
This text examines the efforts and failures of economic experts to make government and public life amenable to measurement, and to re-model society and state in terms of competition. It explores the practical use of economic techniques and conventions by policy-makers, politicians, regulators and judges and how these practices are being adapted to the perceived failings of the neoliberal model. Revised edition includes a new preface from the author and a foreword by Aditya Chakrabortty.
The Disenchantment of Politics: Neoliberalism, sovereignty and economics -- The Promise and Paradox of Competition: Markets, competitive agency and authority -- The Liberal Spirit of Economics: Competition, anti-trust and the Chicago critique of law -- The Violent Threat of Management: Competitiveness, strategy and the audit of political decision -- Contingent Neoliberalism: Financial crisis and beyond -- Afterword: Critique in and of Neoliberalism.
Includes bibliographical references (pages 204-217) and index.
Keywords: Neoliberalism